What is hegemony now? Transformations in media, political economy, and cultural studies - Sean Johnson Andrews (communication +1, 2022)
The basic theoretical framework of Cultural Studies scholarship was forged in an era of nearly unrivaled corporate media hegemony, with most communities finding a limited number of national and multinational corporations transmitting one-way broadcasts to idle consumers whose only agency was in the act of reading ideologies with or against the grain. Likewise, the dominant political economic model in the North was one of expanding social democracy, leading the many strains of the New Left to operate on the presumption that the political economic system will remain as it was: the state would remain as an organ of control over the economy, making the Gramscian concept of hegemony essential to the overall strategy—and the cultural realm a key target for undermining the current reproduction. It is now an accepted commonplace that emergent technologies have changed the way many of us make, distribute, and consume media. The continued dominance of corporate media hegemony is simultaneously aided and hampered by the tenuous system of national segmentations, streaming service overlap and often unenforceable intellectual property rights. And the neoliberal state has effectively ceded the ideological work of the mass media to competing ideoscapes, often funded by wealthy donors with little interest in a functioning public sphere: as long as they can monetize the property or the platform, its ideological content is irrelevant. In this conjuncture, Cultural Studies must reconsider - and reconstitute - its understanding of how hegemony functions and the role that the (transformed) culture industries play in maintaining it.<Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023